ALTERNATIF PENYELESAIAN SENGKETA SEBAGAI PRODUK DARI PLURALISME HUKUM (LEGAL PLURALISM) - Yunimar , (Normative Jurnal Ilmiah Hukum, 2018)
There are many ways that can be done to resolve disputes or disputes, which can be broadly differentiated by litigation or non-litigation. Alternative dispute resolution can be used to resolve disputes that occur in the community based on Law no. 30 of 1999 concerning Arbitration and Alternative Dispute Resolution and Perma No. 1 of 2016 concerning Mediation Procedures in Courts, provided the parties have good faith in resolving their disputes. Alternative dispute resolution as a product of legal pluralism in Indonesia, because in its history during the Dutch colonial period the population of the Dutch East Indies (Indonesia) was divided into several groups of population, and the laws applicable to the population group were different.